Ranking Factors Affecting Organizational Readiness to Implement Enterprise Resource Planning Systems Using Fuzzy-Dimensional Network Analysis. - Zafary, Farzaneh (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2019)
Whenever an organization decides to implement an ERP, it must assess its readiness to implement these complex systems. Therefore, the present study aims at considering the pre-implementation phase of ERP and the factors affecting the readiness of the organization for successful implementation of these systems. In this research, the SWOT matrix was used to classify the identified factors. Moreover, fuzzy-dimensional network analysis was used to evaluate decision options due to the weakness of SWOT technique. Since the factors involved in SWOT analysis are not only disjointed, but sometimes there are relationships among some of its factors. Therefore, internal and external factors of the organization are evaluated and prioritized in the research. In addition, finding the strategic position of the organization and identifying the appropriate strategies and prioritizing them to improve the organization’s readiness for ERP implementation were other tasks in this research. After analyzing the data, 25 organizational factors are prioritized. The numerical results indicated that the organization is in the offensive position therefore, four strategies are designed and prioritized according to its position.